Efficacy of a Student-Led, Community-Based, Multifactorial Fall Prevention Program: Stay in Balance - Der Ananian, Cheryl A.; Mitros, Melanie; Buman, Matthew Paul (Frontiers in Public Health, 2017)
BACKGROUND: Falls are a major public health concern in older adults. Recent fall prevention guidelines recommend the use of multi-factorial fall prevention programs (FPPs) that include exercise for community-dwelling older adults; however, the availability of sustainable, community-based FPPs is limited. METHODS: We conducted a 24-week quasi-experimental study to evaluate the efficacy of a community-based, multi-factorial FPP (Stay in Balance, [SIB]) on dynamic and functional balance, and muscular strength. The SIB program was delivered by allied health students and included a health education program focused on fall risk factors and a progressive exercise program emphasizing lower-extremity strength and balance. All participants initially received the 12-week SIB program and participants were non-randomly assigned at baseline to either continue the SIB exercise program at home or as a center-based program for an additional 12 weeks. Adults aged 60 and older (n=69) who were at risk of falling (fall history or 2+ fall risk factors) were recruited to participate. Mixed effects repeated measures using SAS Proc Mixed were used to examine group, time and group by time effects on dynamic balance [(8 Foot Up & Go)], functional balance [Berg Balance Scale (BBS)] and muscular strength [30 second chair stands and 30 second arm curls]. Non-normally distributed outcome variables were log-transformed. RESULTS: After adjusting for age, gender and body mass index, 8 Foot Up and Go scores, improved significantly over time (F(2,173) = 8.92, p=0.0; T0 – T2 diff = 1.2 [1.0]). Berg Balance Scores (F(2,173) = 29.0, p<0.0001; T0 – T2 diff = 4.96 [0.72]), chair stands (F(2,171) = 10.17, p<0.0001; T0 – T2 diff = 3.1 [0.7]) and arm curls (F(2,3.61) = 12.7, p<0.02; T0 – T2 diff = 2.7 [0.6]) also all improved significantly over time. There were no significant group- by- time effects observed for any of the outcomes. CONCLUSION: The SIB program improved dynamic and functional balance, and muscular strength in older adults at-risk for falling. Our findings indicate continuing home-based strength and balance exercises at home after completion of a center-based FPP program may be an effective and feasible way to maintain improvements in balance and strength parameters.